A melanoma risk score in a Brazilian population Um escore de risco para melanoma em uma população brasileira - Lucio Bakos; Simeona Mastroeni; Renan Rangel Bonamigo; Franco Melchi; Paolo Pasquini; Cristina Fortes (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Important risk factors for cutaneous melanoma (CM) are recognized, but standardized scores for individual assessment must still be developed. OBJECTIVES: The objective of this study was to develop a risk score of CM for a Brazilian sample. METHODS: To verify the estimates of the main risk factors for melanoma, derived from a meta-analysis (Italian-based study), and externally validate them in a population in southern Brazil by means of a case-control study. A total of 117 individuals were evaluated. Different models were constructed combining the summary coefficients of different risk factors, derived from the meta-analysis, multiplied by the corresponding category of each variable for each participant according to a mathematical expression. RESULTS: the variable that best predicted the risk of CM in the studied population was hair color (AUC: 0.71; 95% CI: 0.62-0.79). Other important factors were freckles, sunburn episodes, and skin and eye color. Consideration of other variables such as common nevi, elastosis, family history, and premalignant lesions did not improve the predictive ability of the models. CONCLUSION: The discriminating capacity of the proposed model proved to be superior or comparable to that of previous risk models proposed for CM. FUNDAMENTOS: importantes fatores de risco para melanoma cutâneo são reconhecidos, mas escores padronizados para avaliação individual ainda precisam ser elaborados. OBJETIVOS: o objetivo deste estudo foi desenvolver um escore de risco de melanoma cutâneo para uma amostra brasileira. MÉTODOS: verificar as estimativas dos principais fatores de risco para melanoma, derivado de uma meta-análise (estudo de base italiano) e, externamente, validar em uma população do sul do Brasil por um estudo caso-controle. Um total de 117 indivíduos foram avaliados. RESULTADOS: a variável com maior poder preditivo para o risco de melanoma cutâneo na população estudada foi a cor do cabelo (AUC: 0,71, IC 95%: 0,62-0,79). Outros fatores importantes para o modelo foram: sardas, queimaduras solares, e cor de pele e cor dos olhos. Adicionando outras variáveis, como os nevos comuns, elastose, história familiar e lesões pré-malignas não houve melhora da capacidade preditiva. CONCLUSÃO: A capacidade discriminatória do modelo proposto mostrou-se superior ou comparável aos modelos de risco anteriores propostos para melanoma cutâneo.